Proceedings of the 22nd ACM International Conference on Conference on Information &Amp; Knowledge Management - CIKM '13 2013
DOI: 10.1145/2505515.2505717
|View full text |Cite
|
Sign up to set email alerts
|

Robust models of mouse movement on dynamic web search results pages

Abstract: Understanding how users examine result pages across a broad range of information needs is critical for search engine design. Cursor movements can be used to estimate visual attention on search engine results page (SERP) components, including traditional snippets, aggregated results, and advertisements. However, these signals can only be leveraged for SERPs where cursor tracking was enabled, limiting their utility for informing the design of new SERPs. In this work, we develop robust, log-based mouse movement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 40 publications
(30 reference statements)
1
32
0
Order By: Relevance
“…The utility of mouse tracking has been demonstrated for a number of applications, such as understanding search result page examination [18,19,20], improving results ranking [7,38], and performing relevance predictions [14,16]. Although the importance of mouse tracking data in web search is now evident, very little is known about within-content engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of mouse tracking has been demonstrated for a number of applications, such as understanding search result page examination [18,19,20], improving results ranking [7,38], and performing relevance predictions [14,16]. Although the importance of mouse tracking data in web search is now evident, very little is known about within-content engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Some work distinguishes different types of clicks: first click [8,39], last click [8], long dwell time click [8], satisfied click [39] and only click [8]. Next to clicks, some recent work considers mouse cursor movements on SERPs [16,24,25]. Behavioral signals based on times between user actions.…”
Section: Behavioral Informationmentioning
confidence: 99%
“…Implicit feedback consists for instance of query reformulations [71], mouse clicks [95], mouse movements [48,66,67,73,201], measurements of dwell-time [206]-the time users spend on a website-, or even the time a search result [115]. The advantage of implicit feedback over explicit feedback is that it is available in abundance.…”
Section: Interpreting User Interactionsmentioning
confidence: 99%
“…If a user never looked at a search result, their lack of engagement on this result cannot be indicative of low relevance. A number of studies have shown that mouse movement can be an indicator of user examination of search results, and of specific sections within search results [48,66,67,73,201]. Similarly, in a mobile setting recording how long each part of the screen is visible can be considered an indicator of relevance [115].…”
Section: A/b Testingmentioning
confidence: 99%